2017
DOI: 10.1016/j.wneu.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Subthalamic Nucleus for Deep Brain Stimulation: A Survey Among Parkinson Disease Specialists

Abstract: This survey illustrates that most sites regarded as optimal for STN stimulation are close to each other, but there appears to be no uniform perception of the optimal anatomic target, possibly influencing surgical results. The anatomic sweet zone for STN stimulation needs further specification, as this information is likely to make magnetic resonance imaging-based target definition less variable when applied to individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…Thus, STN border-based programming and the therapeutic VTAs used for reference exhibit the same systematic error, artifactually inflating the measured specificity. When interpreted together with the anatomical diversity of therapeutic activation regions observed across subjects, as reported by earlier studies [24,56], these findings support opportunities for Although this study treats therapeutic tissue activation as a binary variable, presentations of Parkinson disease and its response to STN DBS are known to be multidimensional and varied across patients. A robust body of work suggests that different symptoms may be optimally treated by activation of different subthalamic regions and neural pathways with unique electrophysiological markers [20,26,57,58].…”
Section: Discussionsupporting
confidence: 81%
“…Thus, STN border-based programming and the therapeutic VTAs used for reference exhibit the same systematic error, artifactually inflating the measured specificity. When interpreted together with the anatomical diversity of therapeutic activation regions observed across subjects, as reported by earlier studies [24,56], these findings support opportunities for Although this study treats therapeutic tissue activation as a binary variable, presentations of Parkinson disease and its response to STN DBS are known to be multidimensional and varied across patients. A robust body of work suggests that different symptoms may be optimally treated by activation of different subthalamic regions and neural pathways with unique electrophysiological markers [20,26,57,58].…”
Section: Discussionsupporting
confidence: 81%
“…However, these techniques also have limitations and their efficacy still depends on correct localization of the target. Neuroimaging techniques are advancing, but it is not certain that this will lead to more uniform targeting as experts may define the optimal STN target differently . One study showed that the final stimulation site, based on MER and intraoperative stimulation, was located more lateral and superior than both atlas and MRI based targets .…”
Section: Discussionmentioning
confidence: 99%
“…Saint-Cyr et al, 2002; Herzog et al, 2004; Nowinski et al, 2005; Butson et al, 2011; Welter et al, 2014; Eisenstein et al, 2014]. However, there is still little to no clinical consensus on the specific neural elements (and/or axonal pathways) that are necessary and sufficient for evoking therapeutic effects when stimulated [Hamel et al, 2017]. …”
Section: Introductionmentioning
confidence: 99%